THE IMPACT OF SOCIAL SECURITY ON THE SECURITY POLICY OF THE REPUBLIC OF NORTH MACEDONIA (Religious dialogue and cooperation, 2023)
The concept of national security belongs to the so-called old, traditional approachesto security. Its focus is on the survival of the sovereign state, which is its territorialintegrity and political independence (sovereignty) protected by diplomatic, intelligenceand military capacities, which is ability to repel military aggression or respond successfully.It is therefore justifiably called the concept of state security. In the real socialist countries,state security meant the state of protection of the state from political crime, as wellas the security of the (socialist, communist) regime. Therefore, national or state securitywas in principle divided into so-called external (security from armed aggression) and internal(security of the regime and the state from the internal enemy).The primary bearers of the fight against all occurrences of security threats, as well as thefunctioning of the security function of the state, are the institutions, organizations andsecurity services. The intelligence and security services as an integral part of the securityand intelligence system work to detect, prevent and suppress any occurrence of securitythreats to a particular country or social union. Through the establishment and organizationof a security system or security-intelligence system, the state strives to achieve itsvital interests, to preserve its sovereignty, territorial integrity, constitutional order and thefreedoms and rights of its citizens, in order to achieve the strategic goals of the state -membership in NATO and the European Union, which will bring even greater regional andcontinental security and stability. The focus of the modern concept of national security isthe security of the state, society and the individual. Our country must strive for internalreforms, in terms of restoring the criteria of the rule of law, freedom of the media, controlover the executive branch, which have long been considered unfulfilled.
Keywords: social security; security policy; Macedonia